# Solve for p (10(1-p))÷3=-4÷3

10(1-p)÷3=-4÷3
Rewrite the division as a fraction.
10(1-p)3=-4÷3
Simplify -4÷3.
Rewrite the division as a fraction.
10(1-p)3=-43
Move the negative in front of the fraction.
10(1-p)3=-43
10(1-p)3=-43
Since the expression on each side of the equation has the same denominator, the numerators must be equal.
10(1-p)=-4
Divide each term by 10 and simplify.
Divide each term in 10(1-p)=-4 by 10.
10(1-p)10=-410
Cancel the common factor of 10.
Cancel the common factor.
10(1-p)10=-410
Divide 1-p by 1.
1-p=-410
1-p=-410
Simplify -410.
Cancel the common factor of -4 and 10.
Factor 2 out of -4.
1-p=2(-2)10
Cancel the common factors.
Factor 2 out of 10.
1-p=2⋅-22⋅5
Cancel the common factor.
1-p=2⋅-22⋅5
Rewrite the expression.
1-p=-25
1-p=-25
1-p=-25
Move the negative in front of the fraction.
1-p=-25
1-p=-25
1-p=-25
Move all terms not containing p to the right side of the equation.
Subtract 1 from both sides of the equation.
-p=-25-1
To write -1 as a fraction with a common denominator, multiply by 55.
-p=-25-1⋅55
Combine -1 and 55.
-p=-25+-1⋅55
Combine the numerators over the common denominator.
-p=-2-1⋅55
Simplify the numerator.
Multiply -1 by 5.
-p=-2-55
Subtract 5 from -2.
-p=-75
-p=-75
Move the negative in front of the fraction.
-p=-75
-p=-75
Multiply each term in -p=-75 by -1
Multiply each term in -p=-75 by -1.
(-p)⋅-1=-75⋅-1
Multiply (-p)⋅-1.
Multiply -1 by -1.
1p=-75⋅-1
Multiply p by 1.
p=-75⋅-1
p=-75⋅-1
Multiply -75⋅-1.
Multiply -1 by -1.
p=1(75)
Multiply 75 by 1.
p=75
p=75
p=75
The result can be shown in multiple forms.
Exact Form:
p=75
Decimal Form:
p=1.4
Mixed Number Form:
p=125
Solve for p (10(1-p))÷3=-4÷3

## Our Professionals

### Lydia Fran

#### We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

Scroll to top